The Polygamy of Sheikh Sulaiman Arrasuli: Negotiating Religious Authority and Identity in the Matrilineal Muslim Society of Minangkabau - Armi, Mhd. Ilham; Zulkifli, Zulkifli; Nasri, Ahmad Luthfy (LPPM IAIN Parepare, 2025)
Polygamy in Muslim civilisations has frequently been examined via legal and normative lenses, neglecting its socio-cultural and performative aspects, especially in non-patriarchal social structures. The objective is to examine how polygamy operates not just as a marriage structure but also as a performative mechanism for the construction, negotiation, and legitimisation of religious authority and Muslim identity within a diverse socio-cultural framework. This study utilises a qualitative interpretive methodology based on historical and documentary examination of Sheikh Sulaiman Arrasuli’s life, writings, and socio-religious endeavours. The research employs an interdisciplinary theoretical framework, incorporating Goffman’s dramaturgy for the analysis of public performance and role management, Charles Taylor’s notion of authenticity for identity formation, and Mahmood’s theory of embodied piety for the construction of religious subjectivity. Data are extracted from historical documents, biographical narratives, and previous academic research, and are examined via a socio-cultural framework to reveal patterns of authority negotiation. The findings indicate that polygamy in this setting operated as a culturally ingrained and socially purposeful practice that facilitated the consolidation of religious power within a matrilineal structure. The study indicates that women were not only passive subjects but rather active players in negotiating the meanings and implications of polygamous setups. This work theoretically enhances the comprehension of religious authority as a performative and negotiated construct, rather than as a static result of doctrinal knowledge. It contests prevailing notions that characterise polygamy exclusively as a patriarchal or legal matter. The findings provide insights examination of the connection between polygamy, religious authority, and matrilineal social systems, providing a sophisticated perspective that connects South-east Asian Islamic studies with international discussions on religion, culture, and power